Prevalence of and risk factors associated with depression among nursing students acting on the frontline of COVID-19 pandemic: A cross-sectional study - Nguyen, Huyen Thi Hoa; Hoang, Anh Phuong; Vu, Linh Manh; Tran, Duc Quang; Bui, Linh Khanh; Pham, Thuan Thi; Tran, Linh Thuy Khanh; Nguyen, Huong Thi Thanh (Frontiers in Public Health, 2023)
Introduction: The widespread devastation caused by the ongoing waves of COVID-19 imposed a significant burden on the healthcare labor force. At the frontline in the battle against the deadly COVID-19 virus, nursing students in Vietnam were at a much-increased risk of developing mental health conditions. This study aims to identify the prevalence of depression and its related factors, along with coping strategies used by nursing students in the COVID-19 pandemic in Vietnam. Materials and methods: The research was cross-sectional in nature, with convenient sampling at the epicenters of COVID-19 outbreaks in Vietnam (N=191) from April to November 2021. After conducting a questionnaire pilot, the data was collected strictly using an internet-based approach. The Depression, Anxiety, and Stress Scale – 21 items were used to identify the risk of depression among nursing students. The Chi-square test was used to assess the differences between coping strategies among nursing students. A multivariate logistic regression model was used to identify risk factors associated with depression. Findings: The percentage of nursing students affected by depression was 21.5%, and almost half of the nursing students (49.2%) had no coping strategies for dealing with mental health concerns. Among the remaining nursing students, video-based mental consultation was the most popular method (25.7%). Being females (AOR: 2.7, 95% CI: 1.1–6.7), collecting bio-samples (AOR: 2.9, 95% CI: 1.4–6.2), providing support to vaccination spots (AOR: 2.3, 95% CI: 1.1–5.1), and not vaccinating against COVID-19 (AOR: 3.1, 95% CI: 1.1–9.1) were found as risk factors for depression among nursing students. Conclusions: Our research revealed a significant number of nursing students suffering from depressive symptoms, underscoring the need for more effective methods of dealing with this condition. Additionally, nursing schools should include depression management and coping skills into their curricula so that future nurses are better equipped to handle crisis situations.